Impact of Diesel Engine Exhaust Gases on Environmental Pollution and Human Health - Ivan Mavrin; Damir Knežević; Ivo Jurić (Promet (Zagreb), 2004)
Fine particles that can be found in the exhaust gases of dieselengines and have a diameter of 2. 5 !Jl1l and ultra-fine particlesof 0.1 !Jl1l in diameter are mainly products of the combustionprocess. Experiments on animals have proven that theparticulates from the ambient air can cause damage to thelungs and can even end fatally. Therefore, it is necessary to reducethe mass of fine particles in the atmosphere and the numberof ultra-fine particles. Numerous studies of experiments onanimals have proven the toxicity of these particles. The air saturatedby particles resulted in cardio-pulmonary diseases in animalmodels. The epidemiological studies have shown the interdependenceof the increase in mortality and morbidity, especiallyin the elderly and persons suffering from respiratory ailmentsand cardio-vascular diseases. A hypothesis has been setthat the ultra-fine particles cause inflammatory reactions in alveoliand interstitium resulting in the increase of blood coagulationand deterioration of the condition in persons sufferingfrom the problems in cardio-vascular system.